2022
DOI: 10.1097/md.0000000000031100
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficacy and safety of dolutegravir plus lamivudine versus tenofovir plus lamivudine and efavirenz in ART-naïve HIV-1-infected adults

Abstract: Limited real-world data on dolutegravir (DTG) plus lamivudine (3TC) for HIV-1-infected individuals have been reported. This study aimed to evaluated the real-world efficacy and safety of DTG + 3TC in ART-naïve HIV-1-infected adults in China. This real-world prospective observational cohort study enrolled HIV-1-infected adults receiving ART initiation with DTG + 3TC (D3 group) or tenofovir plus lamivudine and efavirenz (TDF + 3TC + EFV, TLE group) with subgroups of low viral load (LVL, ≤500,000 copies/mL) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Three cohort studies included 581 PLWH who received DTG plus 3TC and were followed for a median of 48 weeks [ 39 , 49 , 50 ] ( Supplementary Table S2 ). Two studies were from Spain, and one was from China.…”
Section: Resultsmentioning
confidence: 99%
“…Three cohort studies included 581 PLWH who received DTG plus 3TC and were followed for a median of 48 weeks [ 39 , 49 , 50 ] ( Supplementary Table S2 ). Two studies were from Spain, and one was from China.…”
Section: Resultsmentioning
confidence: 99%
“…So far, several observational studies have compared the clinical outcomes between TLE and DTG + 3TC or TLE and B/F/TAF in treatmentnaïve individuals, respectively, and all have consistently showed that either DTG + 3TC or B/F/TAF was superior to TLE in terms of rapid decline in VL or regimen persistence. [14][15][16] However, we still lack comparative data in regard to efficacy and safety of DTG + 3TC and B/F/ TAF in ART-naïve individuals in a real-life scenario. Therefore, we conducted this study to fill this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…Three cohort studies included 581 PLWH who received DTG plus 3TC and were followed for a median of 48 weeks [39,49,50] (Supplementary Table 2). Two studies were from Spain, and one was from China.…”
Section: Art-naïve Plwhmentioning
confidence: 99%